Factors Affecting the Attraction and Retention of Generation Z employees in the Vietnamese F&B industry. - Tran, Phuong Vy; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The aim of the thesis is to investigate the factors that influence the attraction and retention of Generation Z human resources in the F&B industry in Vietnam. Currently, the F&B industry in Vietnam is an industry with great development potential and, in particular, attracts a large number of young Generation Z resources to participate in the industry. The thesis focuses on the analysis of the top 5 factors influencing the decision to enter and stay in the F&B sector among Generation Z workers in Vietnam. In this context, we examine the following topics: work-life balance, career growth opportunities, company culture, leadership styles, competitive compensation and benefits. The research method of this paper is a quantitative method through a survey of Generation Z employees in Vietnam in community groups on social media. Through multiple choice questions and Likert scale statements, etc. to clarify the influence of each factor in creating key motivations for attracting and retaining Generation Z employees. The study provides insights into the dynamics of Generation Z in Vietnam for F&B industry stakeholders to adapt their operations, foster an attractive work environment, and effectively attract and retain talented workers, thereby enhancing organizational resilience and market success.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses